Human mesenchymal stromal cells transplanted into mice stimulate renal tubular cells and enhance mitochondrial function. Issue 1 (December 2017) - Perico, Luca; Morigi, Marina; Rota, Cinzia; Breno, Matteo; Mele, Caterina; Noris, Marina; Introna, Martino; Capelli, Chiara; Longaretti, Lorena; Rottoli, Daniela; Conti, Sara; Corna, Daniela; et al.
Abstract Mesenchymal stromal cells (MSCs) are renoprotective and drive regeneration following injury, although cellular targets of such an effect are still ill-defined. Here, we show that human umbilical cord (UC)-MSCs transplanted into mice stimulate tubular cells to regain mitochondrial mass and function, associated with enhanced microtubule-rich projections that appear to mediate mitochondrial trafficking to create a reparative dialogue among adjacent tubular cells. Treatment with UC-MSCs in mice with cisplatin-induced acute kidney injury (AKI) regulates mitochondrial biogenesis in proximal tubuli by enhancing PGC1α expression, NAD+ biosynthesis and Sirtuin 3 (SIRT3) activity, thus fostering antioxidant defenses and ATP production. The functional role of SIRT3 in tubular recovery is highlighted by data that in SIRT3-deficient mice with AKI, UC-MSC treatment fails to induce renoprotection. These data document a previously unrecognized mechanism through which UC-MSCs facilitate renal repair, so as to induce global metabolic reprogramming of damaged tubular cells to sustain energy supply. Mesenchymal stromal cells drive renal regeneration following injury. Here, the authors show that human mesenchymal stromal cells, when transplanted into mice with acute kidney injury, stimulate renal tubular cell growth and enhance mitochondrial function via SIRT3.